Implikasi Hukum pada Transeksual terhadap Pembagian Waris Perspektif Hukum Islam dan Hukum Positif di Indonesia - Hapsari, Vivi; Hidayat, Riyan Erwin (Syakhsiyah Jurnal Hukum Keluarga Islam, 2023)
Transsexual in Indonesia are considered deviants, although the phenomenon of Transsexual in our society is no longer a new fact, deviant behavior is still considered abnormal and even considered a disease. Transsexuals are prohibited by Islam as stated in the Al-Qur'an and hadith, this is contrary to the positive law in Indonesia where Transsexuals enjoy legal legality. The legality and legal status obtained by Transsexuals in Positive Law in Indonesia has a big impact in various aspects. One aspect that is affected by the existence of Transsexuals is Inheritance Law. This research aims to determine the legal implications for Transsexual perpetrators in the distribution of inheritance from the perspective of Islamic Law and Positive Law in Indonesia. This research is normative legal research which refers to literature studies in the field of law using a conceptual problem approach and a case approach. The research findings show that the law of changing sex on purpose is not permissible according to Islamic law. This is in accordance with the word of God in the Qur'an, the Hadith of the Prophet, and the MUI Fatwa. With the legalization of a Court Order, it raises two implications or possibilities that lead to opposite results. On the one hand, the distribution of inheritance must be in accordance with the initial gender at birth and on the other hand, the distribution of inheritance can be adjusted to the new gender in accordance with the legality obtained from the court's decision.